2016 15th IEEE International Conference on Machine Learning and Applications (ICMLA) 2016
DOI: 10.1109/icmla.2016.0132
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying Detection with a Pronunciation Based Convolutional Neural Network

Abstract: This paper describes the process of building a cyberbullying intervention interface driven by a machine-learning based text-classification service. We make two main contributions. First, we show that cyberbullying can be identified in real-time before it takes place, with available machine learning and natural language processing tools, in particular convolutional neural networks. Second, we present a mechanism that provides individuals with early feedback about how other people would feel about wording choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 17 publications
0
57
0
1
Order By: Relevance
“…Some works observed that the content information in social media has many incorrect spellings, and in some cases, the users in social media intentionally obfuscate the words or phrases in the sentence to evade the manual and automatic detection. 23,24 These extra words will expand the vocabulary and affect the various performances of the algorithm. Waseem and Hovy performed a grid search over all possible feature set combinations.…”
Section: Cyberbullying Detectionmentioning
confidence: 99%
“…Some works observed that the content information in social media has many incorrect spellings, and in some cases, the users in social media intentionally obfuscate the words or phrases in the sentence to evade the manual and automatic detection. 23,24 These extra words will expand the vocabulary and affect the various performances of the algorithm. Waseem and Hovy performed a grid search over all possible feature set combinations.…”
Section: Cyberbullying Detectionmentioning
confidence: 99%
“…It helped to develop gender based approach to classify discrimination which was a type used for bullying [10] [11]. Another type of detecting cyberbullying is by using deep learning and by using neural networks to reduce the problem of unwanted data and bullying data [6]. Then later with increase in use of local abusive language they further developed supervised classification techniques (algorithms that learn from labelled data) with categorizing text data by NLP (Natural Language Processing) feature to analyze the data which was better than deep learning approach [7].…”
Section: Related Workmentioning
confidence: 99%
“…Another type of approaches using Deep Learning and Neural Networks. One of the proposed methods is Zhang et al [11] in their paper uses novel pronunciation based convolution neural network (PCNN), thereby alleviating the problem of noise and bullying data sparsity to overcome class imbalance. 1313 messages from twitter, 13,000 messages from formspring.me.…”
Section: Related Workmentioning
confidence: 99%